Development Of Work Sheets (LKPD) For Students In Japanese Population History In Indonesia Based On Characters For Class XI SMA Negeri 1 Pasirsakti - Umi Hartati; Rizki Ahmad Refa’i (Criksetra: Jurnal Pendidikan Sejarah, 2019)
The objectives of the study were (1) to analyze the learning process of class XI history; (2) determining the historical LKPD-based design of character values on the historical material of the Japanese Occupation in Indonesia; (3) to analyze the worth of LKPD history based on character values on the history material of the Japanese occupation in Indonesia. Research methods used research and development (R & D). Type of research is a development model adapted from research Sugiyono Level 1, (produce design but not test try). Stages of research starts from the needs analysis by collecting information through observation, interview. Continue to design the product. After generating the product draft validation is done by a team of experts ie design experts, material experts, history teachers and class XI student responses as users, then proceed with product revision, the revision is feasible to be tested. The results of the research are (1) historical learning tools compiled based on the revision of the 2013 curriculum, and learning resources used in the learning process of the Indonesian history package book, internet and the lack of character-based LKPD development; (2) LKPD is designed with character-based, (3) LKPD based character value development result validated by design expert phase 1 of 78.71%, stage 2 of 90% (14% increase). The result of validation by material expert of phase 1 is 85.71%, stage 2 is 100% (14.29% increase). and student responses of 95%. Validation results are categorized as "Very Eligible". Based on the validation results indicate that LKPD-based character value is feasible to be tested.